Extensive pulmonary sarcoid reaction in a patient with BMPR-2 associated idiopathic pulmonary arterial hypertension - Braam, Evelien A.J.E.; Quanjel, Marian J.R.; van Haren-Willems, Jolanda H.G.M.; van Oosterhout, Matthijs F.M.; Vink, Aryan; Heijdra, Yvonne F.; Kwakkel-van Erp, Johanna M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Pulmonary arterial hypertension is a progressive life-threatening disease characterized by vascular remodeling. There is evidence that varied immune mechanism play an important role in progression of pulmonary hypertension.  We describe a case of a 35-year-old woman with idiopathic pulmonary arterial hypertension (IPAH) and a novel BMPR2 mutation, who underwent a successful lung transplantation.  Extensive granulomatous inflammation was seen in the resected lungs. The granulomatous inflammation found in the histology supports  a sarcoid-like reaction due to pulmonary hypertension in the context of the BMPR2 mutation.